Talent Development Practises at Higher Education Institutions in Malaysia during COVID-19 Pandemic: A Case of a Public University in the Southern Region - Omar, Siti Sarah; Mohd Angsor, Mohd Asmadi; Tan, Angeline Jia Min (Journal of Technology Management and Business, 2023)
Talent Development (TD) is important for every institution, including higher education. However, few institutions regard TD as one of their most crucial elements. During Covid-19, academics experienced stress and faced challenges when they had to alter their regular teaching and learning activities, such as switching to an online learning platform during the pandemic. This study, therefore, examined how the pandemic has affected TD practises in higher education institutions as human capital is the most important resource to an organisation. The research objective was to examine TD practises at a public Higher Education Institution (HEI) in Malaysia during the pandemic. This study employed a qualitative research methodology, namely phenomenological interviews, which enabled the researcher to capture the respondents’ actual experiences. In this study, two HR representatives and two academics from the same university participated as interviewees. Performance management, coaching, leadership development, and talent acquisition were themes that emerged from the interviews, along with several subthemes like hybrid, webinar courses, talent pool, and requirements. This study is significant in that it highlighted the value of TD practises in the higher education sector, particularly during the COVID-19 pandemic. In addition, as a guide for HEI administrators, this study helps in the revision of their existing strategies and understanding of the capacity gaps between the current academic skill level and the changing employment requirements to ultimately establish a coordinated TD.